Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
C.
Step-by-step explanation:
This is substitution method in solving simulteanous equations.
given y = 4x + 1
we will substitute y into 2y = -x-1
[tex]2(4x + 1) = - x - 1 \\ 8x + 2 = - x - 1 \\ 8x + x + 2 = - 1 \\ 9x + 2 = - 1 \\ 9x = - 1 - 2 \\ 9x = - 3[/tex]
Therefore the answer is C.
SOLVING
[tex]\Large\maltese\underline{\textsf{A. What is Asked}}[/tex]
Substituting the equation given into another equation will produce another equation. But which one?
[tex]\Large\maltese\underline{\textsf{B. This problem has been solved!}}[/tex]
[tex]\bf{2y=-x-1}[/tex] | substitute the required equation
[tex]\bf{2(4x+1)=-x-1}[/tex] | solve in terms of x
[tex]\bf{8x+2=-x-1}[/tex] | carry on solving
[tex]\bf{9x+2=-1}[/tex] | carry on solving
[tex]\bf{9x=-3[/tex]
[tex]\cline{1-2}[/tex]
[tex]\bf{Result:}[/tex]
[tex]\bf{=The\;third\;option}[/tex]
[tex]\LARGE\boxed{\bf{aesthetics\not1\theta 1}}[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.